PINGS (Phone-Based Intervention Under Nurse Guidance After Stroke): Interim Results of a Pilot Randomized Controlled Trial. Issue 1 (January 2018) - Sarfo, Fred; Treiber, Frank; Gebregziabher, Mulugeta; Adamu, Sheila; Patel, Sachin; Nichols, Michelle; Awuah, Dominic; Sakyi, Asumadu; Adu-Darko, Nyantakyi; Singh, Arti; Tagge, Raelle; Carolyn, Jenkins; et al.
Abstract : Background and Purpose—: Stroke exacts an immense toll in sub-Saharan Africa where there are few resources, and stroke prevention research is limited. The aim of this study is to test the feasibility and preliminary efficacy of an m-Health technology–enabled, nurse-guided intervention in improving blood pressure (BP) control among Ghanaian stroke patients within 1 month of symptom onset. Methods—: We conducted a 2-arm cluster pilot randomized controlled trial involving 60 recent stroke survivors encountered within a single tertiary medical system in Ghana. Subjects in the intervention arm (n=30) received a Blue-toothed UA-767Plus BT BP device and smartphone for monitoring and reporting BP measurements and medication intake for 3 months compared with standard of care (n=30). Primary outcome measure was systolic BP <140 mm Hg at month 3; secondary outcomes included medication adherence and autonomous self-regulation. Analysis accounting for clustering was made using generalized linear mixed model by intention to treat. Results—: Mean±SD age was 55±13 years, 65% male. Systolic BP <140 mm Hg at month 3 was found in 20/30 subjects (66.7%) in the intervention arm versus 14/30 subjects (46.7%) in the control arm ( P =0.12). Medication possession ratio scores at month 3 were better in the intervention (0.88±0.40) versus control (0.64±0.45) arm ( P =0.03). One subject in control arm died from a recurrent hemorrhagic stroke. Conclusions—: It is feasible to conduct an m-Health–based, nurse-guided BP control intervention among recent stroke patients in sub-Saharan Africa. We observed a potential signal of efficacy with the intervention, which will need to be tested in a future large definitive study. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02568137. Abstract : Supplemental Digital Content is available in the text.